Discourse representations: appraisals of the gay community in the Chilean cyber press - Araya Seguel, Claudio (Árboles y Rizomas, 2019)
In recent years there have been legal changes that seek for a new treatment for the lesbian, gay, bisexual, transsexual, intersex (LGBTI) community in Chile. These changes have materialized in legislation such as the antidiscrimination and the Civil Union Agreement (AUC) laws enforced in October 2015, as well as political decisions such as the publication and distribution of a story about a homoparental family in the network of State kindergartens. The doubt that arises in this scenario is whether the media discourse and the Chilean readership of cyberpress is in tune with these changes coming from the State. In this context, this article critically examines the discursive representations about the gay community in opinion forums in two newspapers with a conservative profile. These discursive representations are obtained from a linguistic analysis, from the semantic value system, of the clause complexes found in the comments. The objective is to examine how, through readers' discourse, the social identity of the gay community is configured and how a type of homophobic discrimination is exercised through linguistic resources. The most salient results indicate that the gay community and the homoparental story are generally negatively evaluated. This evaluation is based on a sanction judgment and social esteem linked to abnormality and immorality and a heteroglossic commitment that recognizes the positions of diversity through the dialogic contraction.
Keywords: gay community; Appraisal; discourse representations; cyberpress